Perancangan Aplikasi Katalog Perpustakaan Dengan Menerapkan Algortima Boyer Moore - Arifa, Nabila Rahmi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Libraries as representative providers of information. This means that the life and existence of a library can be a chain of history for the past, a root for life in the present and a guide for moving into the future. Information services consist of five aspects, namely information collection, information preservation, information processing, information utilization and information dissemination. String maching uses the Boyer Moore Algorithm to match patterns that will be searched for from the library catalog, so that the matches in pattern selection can be seen. It is hoped that the Boyer Moore Algorithm can complete matching in the introduction of library catalogues, so that it can help students, workers and the public in searching the library catalogue